Geodynamic network of the Argentina Islands nearby to the Ukrainian Antarctic station Akademik Vernadsky - P. Bahmach; V. Glotov; Yu. Ladanovskiy; K. Tretyak (Ukrainian Antarctic Journal, 2003)
Within the framework of the 8-th seasonal Ukrainian Antarctic Expedition (8-УАЕ) during February, 2003 the precision geodetic network of the islands adjacent to the station Vernadsky has been created by general efforts of the workers of National University “ Lviv Polytechnic ” and “ECOMM Co.”. The purpose of this project is to create a basic geodetic network both for the topographical-geodesic survey and determination of quantitative and qualitative parameters of deformations and movement of the terrestrial surface of the Antarctic peninsula. The accuracy of measurements of scheduled coordinates practically in every item of the network is within 0,8-2,5 mm, and height accuracy – within 1,0-3,2 mm. The realization of reiterated measurements will permit to improve the modern regional geodynamic model of the Antarctic peninsula.